Comparison of Cerebral Perfusion in Perimesencephalic Subarachnoid Hemorrhage and Aneurysmal Subarachnoid Hemorrhage - Fragata, I (2021)
Purpose: Perimesencephalic hemorrhage (PMH) is a benign subtype of nonaneurysmal subarachnoid hemorrhage (SAH). We aimed to investigate if cerebral perfusion in PMH is less affected than in aneurysmal SAH (aSAH). Methods: From a prospective cohort of 80 patients with spontaneous SAH, we included PMH patients (n = 15) and selected aSAH patients (n = 39) with similar clinical grade at admission (World Federation of Neurosurgeons Scale-WFNS I/II). Computed tomography (CT) perfusion was performed at < 72 h and/or at 8-10 days. Cerebral perfusion parameter values were compared between groups with nonparametric tests. Subgroup analyses compared PMH and aSAH patients stratified according to aneurysmal location (anterior or posterior circulation) and blood burden (Fisher grade). Results: At < 72 h, no significant differences in perfusion parameters were found between PMH and aSAH patients. At 8-10 days, PMH patients had lower MTT than aSAH patients, and a trend for higher CBF. PMH patients had higher CBF and CBV at < 72 h when compared to posterior circulation aSAH patients. When compared to aSAH patients with similar blood burden, PMH patients had higher CBF and lower MTT at < 72 h, and lower MTT at 8-10 days. Conclusion: PMH patients had better cerebral perfusion compared to patients with aSAH, particularly during the vasospasm time window. After stratifying for the amount of blood, PMH patients also had better cerebral perfusion in the first 72 h after SAH. These results are in line with the better clinical presentation and prognosis of PMH, and possibly with a different etiology.